Faktor Kualifikasi Kontraktor yang Mempengaruhi Kinerja Proyek Konstruksi Berdasarkan Persepsi Konsultan - Lioni, C.Z.; Fahirah, F.; Hakim, L. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
The development of quality infrastructure in Sigi Regency plays a vital role in supporting economic growth and community welfare, particularly in the aftermath of the 2018 earthquake. The success of this development is significantly influenced by contractor qualifications, which encompass technical aspects, experience, and available resources. This study aims to identify the dominant contractor qualification factors influencing construction project performance and to analyze the relationships among these factors based on the perceptions of consultants in Sigi Regency. This study employed a quantitative approach, distributing questionnaires to 37 consultants selected through purposive sampling. Data from 24 variables were analyzed using descriptive statistics, the Relative Rank Index (RRI), and Spearman's Rho correlation. The RRI analysis identified five dominant factors: financial obstacles during project implementation (RRI = 0.874), labor experience (RRI = 0.869), the educational background of the person-in-charge (RRI = 0.847), compliance with technical specifications (RRI = 0.815), and the educational background of implementers and supervisors (RRI = 0.811). The Spearman correlation analysis revealed a strong relationship between the educational backgrounds of implementers and the person-in-charge (r = 0.668). However, the financial obstacles factor showed a very weak correlation with the other four variables. This study underscores that human resource competency and financial readiness are critical factors for enhancing construction project performance in Sigi Regency.